Neuroprotective effect of lovastatin through down-regulation of pro-apoptotic Mst1 gene expression in rat model pilocarpine epilepsy. (3rd October 2018) - Abdanipour, Alireza; Deheshjo, Fatemeh; Sohrabi, Davood; Jafari Anarkooli, Iraj; Nejatbakhsh, Reza
ABSTRACT: Objective: Statins as inhibitors of HMG-CoA reductase have been recently recognized as anti-inflammatory and neuroprotective drugs. In this paper, we studied anti-apoptotic and regulatory effects of lovastatin using Pilocarpine rat model through downregulation of  Mst1  (Mammalian sterile 20-like kinase 1) as a novel pro-apoptotic gene. Methods: The rats were divided into four groups: non-treated epileptic rats, lovastatin treated, and two vehicle groups. Racine scale was used for behavioral assessment and animals with a score of 4–5 were selected for the study. After 3 days, epileptic rats received intraperitoneal injections of lovastatin, followed by treating for 14 days. Next, they were sacrificed (28 post-first seizure) and prepared for histopathological analysis and Real-time RT-PCR. Results: The results showed that lovastatin protects Pilocarpine-induced cell death via a regulatory effect on pro-apoptotic and anti-apoptotic gene expression. The real-time PCR results showed that in the epileptic lovastatin treated group, the expression level of  Mst1 significantly decreased while  Nrf2  and  Bcl-2  genes increased. Furthermore, histological analysis of neurodegeneration in the brain sections showed that the number of hippocampal apoptotic cells significantly decreased in the treatment groups. The results showed that the numerical density of neurons per area was significantly higher in the treated than the untreated group. Conclusion: Overall, the results of this study showed that lovastatin attenuates hippocampal cell death in Pilocarpine-induced status epilepticus rat model through downregulation of the pro-apoptotic Mst1 gene. Abbreviations: Mst1 : Mammalian sterile 20-like kinase 1; Nrf2 : nuclear factor erythroid 2–related factor 2; Bcl-2 : B-cell lymphoma 2; HMG-CoA: 3-hydroxy-3-methylglutaryl-coenzyme A; RT-PCR: reverse transcription-polymerase chain reaction; TLE: Temporal Lobe Epilepsy; SE: status epilepticus.